Clinical features, management and mortality in diabetic and non-diabetic patients with heart failure – observations from the COMMIT-HF registry - Siedlecki, Łukasz; Szyguła-Jurkiewicz, Bożena; Pyka, Łukasz; Król, Bogumiła; Szczurek, Wioletta; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Diabetes mellitus (DM) and heart failure (HF) are two common diseases that often co-exist. Aim : To explore clinical characteristics, management strategies and rates of 3-year mortality among diabetic and non-diabetic patients hospitalised in a highly specialized interventional cardiology centre. Material and methods : We used data from COMMIT-HF (COnteMporary Modalities In Treatment of Heart Failure), which is a single-centre, observational, prospective registry of patients with symptomatic chronic systolic HF (LVEF < 35%). Data collected included demographics, clinical characteristics, medical history, inpatient therapies and procedures. Follow-up was based on the information acquired from the national health-care provider. Results : We analysed 1397 patients out of the total of 1798 patients included in the COMMIT-HF registry between 2009 and 2013. We identified 595 (42.6%) diabetic and 802 (57.4%) non-diabetic patients. Compared to patients without DM, patients with type 2 DM had a higher rate of comorbidity. Frequency of death in patients with DM during the 3-year follow-up was significantly higher than in patients without DM (199 (33.4%) vs. 163 (20.3%), p < 0.0001, respectively). Conclusions : In the analysed HF population representing patients receiving typical, everyday clinical care, the prevalence of DM is 42.6%. Diabetes mellitus has deleterious effects on renal function and symptoms as assessed by the New York Heart Association functional class. DM remains associated with increased frequency of death in patients with HF, in spite of recent pharmacological and device-based advances in HF management.